Hubungan Penggunaan Google Classroom dengan Hasil Belajar Siswa pada Mata Pelajaran Simulasi Digital Kelas X di SMKN 1 Ampek Angkek - Warrahmah, Annisa Mawaddah; Zakir, Supratman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The research was conducted because currently the implementation of learning is carried out using an online system. The purpose of this study was to determine the relationship between the use of Google Classroom and student learning outcomes at SMKN 1 Ampek Angkek. In addition, to find out the obstacles faced by teachers and students in the use of online learning. The subjects or respondents in this study were class X students of the Department of Fashion Design (TB) and Office Administration Automation (OTDP) with a total of 128 students and taking a sample of 56 students from a population of students who were randomly selected without regard to the strata in the population. The method used in this research is the Quantitative Method. The instrument used was a questionnaire filled out bystudents in the form of implementing learning using Google Classroom (Variable X) and LearningOutcomes (Variable Y). The data analysis technique was carried out with Validity, Reliability,Normality Test, Linearity Test, Hypothesis Testing, and R Square Test to find out how big the relationship between the use of Google Classroom and student learning outcomes. Judging from thevalue of sig.(2-teiled) each Variable X and Variable Y is <0.005. Judging from the values of rcount andrtable, the result is that the value of rcount > rtable. rtable value 0.254. Variable X has a value ofCronbach's alpha > 0.006, that is, Variable X has a value of 0.869. Thus, the design of the questionnaire statement on the variable using Google Classroom is reliable. The value of R is 0.703, which means that the independent variable (Use of Google Classroom) is able to explain the dependent variable (Learning Outcomes) of 49.42%. The results of this study indicate that there is a significant positive relationship between the use of Google Classroom and learning outcomes.